IMPLEMENTATION OF THE LOCATION BOOK ON STUDENTS' CHARACTERISTICS IN AL-UKHUWAH INTERGRAL MADRASA IBTIDAIYAH - Muhammad Nasir; Husin; Ayunda Fitriani; Abdul Rashid bin Abdul Aziz (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
Deviant behavior among adolescents has always been a concern in itself. Therefore parents must rise to carry out their obligations to children, in the form of supervision, attention, and good education, so that later they become generations that can benefit other Muslims. Madrasah Ibtidaiyah Integral Al-Ukhuwah banjang uses a contact book as a means to shape the morals of its students. The contact book has programs that must be filled out by the homeroom teacher for activities at school and programs that must be filled out by parents for activities at home. This study aims to find out how the implementation of the contact book program affects student morals at Madrasah Ibtidaiyah Integral Al-Ukhuwah, Amuntai Regency, South Kalimantan Province. This study uses a descriptive qualitative method. The techniques used to collect data are observation, interviews and documentation. The results of this study indicate that the contact book is made within a framework of intention to build effective communication between parents and schools to shape student morals, there is an influence from the application of the contact book on student morals, including discipline in worship, social, and self-reliance.